The Effect of Service Quality and Facilities on Visitor Satisfaction at Gandoriah Beach, Pariaman City - masriki .; Aldri Frinaldi (International Journal of Tourism, Heritage and Recreation Sport, 2020)
The main objective of this study was to examine the effect of service quality and facility quality on visitor satisfaction at Gandoriah Beach, Pariaman City. This study uses a quantitative approach. The population of this research is 104,709 tourists visiting Gandoriah Beach. The sample in this study consisted of 398 respondents who were determined using the Slovin formula with an error rate of 5% and the acquisition was made through accidental sampling. Data analysis techniques used multiple regression analysis. The findings show that there is a significant influence between the quality of services and facilities individually to the satisfaction of visitors at Gandoriah Beach, Pariaman City at 57.6% and 45.6%. The joint effect of service and facility quality on visitor satisfaction at Gandoriah Beach, Pariaman City was 57.7%. The results of the study concluded that the quality of services and facilities had an effect on the satisfaction of visitors both together and individually in Gandoriah Beach, Pariaman City.